A case of inappropriate non-neoplastic secretion of TSH treated with bromocriptine - (:unkn) unknown (My University, 1993)
A 67 year old patient with overt signs of hyperthyroidism had high serum TSH values in addition to high T3 and T4 values. Initial treatment with propyltiouracil (PTU) reduced the high serum thyroid hormone levels but TSH levels were further increased. With an augmented TSH response to TRH and negative sella tomography, diagnosis of inappropriate secretion of TSH was made. PTU was stopped and bromocriptine 10 mg daily given with perfect result in 18 weeks. The patient is euthyroid on bromocriptine therapy.
Keywords: Female; Humans; Aged; Bromocriptine; Hyperthyroidism; Pituitary Diseases; Thyrotropin; Thyroxine; Triiodothyronine